Microbicide clinical trial adherence: insights for introduction. Issue 1 (8th April 2013) - Woodsong, Cynthia; MacQueen, Kathleen; Amico, K Rivet; Friedland, Barbara; Gafos, Mitzy; Mansoor, Leila; Tolley, Elizabeth; McCormack, Sheena
Abstract : After two decades of microbicide clinical trials it remains uncertain if vaginally‐ delivered products will be clearly shown to reduce the risk of HIV infection in women and girls. Furthermore, a microbicide product with demonstrated clinical efficacy must be used correctly and consistently if it is to prevent infection. Information on adherence that can be gleaned from microbicide trials is relevant for future microbicide safety and efficacy trials, pre‐licensure implementation trials, Phase IV post‐marketing research, and microbicide introduction and delivery. Drawing primarily from data and experience that has emerged from the large‐scale microbicide efficacy trials completed to‐date, the paper identifies six broad areas of adherence lessons learned: (1) Adherence measurement in clinical trials, (2) Comprehension of use instructions/Instructions for use, (3) Unknown efficacy and its effect on adherence/Messages regarding effectiveness, (4) Partner influence on use, (5) Retention and continuation and (6) Generalizability of trial participants' adherence behavior. Each is discussed, with examples provided from microbicide trials. For each of these adherence topics, recommendations are provided for using trial findings to prepare for future microbicide safety and efficacy trials, Phase IV post‐marketing research, and microbicide introduction and delivery programs.